The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00248-011-9815-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Microbial Colonization of a Dolostone Quarry: Implications for Stone Biodeterioration and Response to Biocide Treatments

Abstract: This study examines the microbial colonization of three fronts of an abandoned dolostone quarry (Redueña, Madrid, Spain) exposed to atmospheric conditions for different time periods since Roman times to the present. Through scanning electron microscopy in backscattered electron mode (SEM-BSE), endolithic colonization was predominantly detected in the most recently exposed front, while in the longer exposed quarry fronts, epilithic forms of growth were most often observed. These observations were confirmed by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…Consistently with other non-polar dryland habitats (Lee et al, 2016), pioneering studies in Antarctica suggested that the edaphic and lithic niches differed in microbial community composition (Pointing et al, 2009;Makhalanyane et al, 2013;Yung et al, 2014;Van Goethem et al, 2016). Evidence based on the rock colonization rate after biocide treatments suggests that changes in lithobiontic communities may occur even over short periods of time (Cámara et al, 2011), but how these differences are established and evolve over time for different types of microorganisms remains unexplored.…”
Section: Introductionmentioning
confidence: 80%
“…Consistently with other non-polar dryland habitats (Lee et al, 2016), pioneering studies in Antarctica suggested that the edaphic and lithic niches differed in microbial community composition (Pointing et al, 2009;Makhalanyane et al, 2013;Yung et al, 2014;Van Goethem et al, 2016). Evidence based on the rock colonization rate after biocide treatments suggests that changes in lithobiontic communities may occur even over short periods of time (Cámara et al, 2011), but how these differences are established and evolve over time for different types of microorganisms remains unexplored.…”
Section: Introductionmentioning
confidence: 80%
“…In these conditions, the prevention of biofouling growth can be achieved either by the selection and application of high resistance coating materials to natural thermooxidative processes (thermal stress and UV action [6,13,14,16] and the molds action [8,10,15]), or through the use of appropriate antifungal biocides [35][36][37][38][39][40][41] (obviously with the necessary precautions -taking into account that the investigated bridge is in the Natura 2000 protected area [24]).…”
Section: Resultsmentioning
confidence: 99%
“…Remediation protocols for stone degradation by biological attack include the use of biocides or sterilization by UV light, but their effect is often limited to the surface of the material treated [16][17][18] and, in the case of biocides, irreversible damaging side effects may be induced on the rock materials.…”
Section: Introductionmentioning
confidence: 99%